The spy who came in from the cold. - Le Carre, John 1931- (Doward-McCann, 1963)
A veteran spy wants to "come in from the cold" to retirement. He undertakes one last assignment in which he pretends defection and provides the enemy with sufficient evidence to label their leader a double agent.